PERANAN KELOMPOK PETANI MUDA DALAM PENINGKATAN PENDAPATAN USAHATANI PADI SAWAH (STUDI KASUS DESA PAPE KECAMATAN BAJAWA KABUPATEN NGADA) - Igniosa Taus; Mersiana Tawa (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2026)
Farming business activities require the role of farmer groups as production units and effective and optimal management of land, labor, and capital are supporting variables that influence the increase in production intensity. The purpose of this study is to examine the relationship between the role of farmer groups in carrying out their agricultural business activities and to analyze the income of rice farming businesses in Pape Village, Bajawa District. Study data shows that farmer groups are still not optimal in carrying out their function as production units to realize cooperasion in achieving a more efficient and economically profitable business scale. Farmersexperience losses as seen from the amount of income obtained through rice farming in the June - September 2025 planting season which is IDR 2,987,000 with a rasio of 0.64% or R/C less than 1 indicating that the rice farming business of farmer groups is experiencing losses and is not yet feasible to be cultivated. Key words: Pape Village, Business Feasibility, Paddy Fields, Young Farmers, Agricultural Productivity